Response Time Considerations in Realtime Software Design - Sellappan, Palaniappan (Malaysian Journal of Computer Science, 2017)
Identifies several factors that affect the design of realtime software and then discusses some approaches that a software developer may use to meet the inherent timing requirements of realtime software.